2020
DOI: 10.1016/j.ajhg.2020.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Bi-allelic Variations of SMO in Humans Cause a Broad Spectrum of Developmental Anomalies Due to Abnormal Hedgehog Signaling

Abstract: The evolutionarily conserved hedgehog (Hh) pathway is essential for organogenesis and plays critical roles in postnatal tissue maintenance and renewal. A unique feature of the vertebrate Hh pathway is that signal transduction requires the primary cilium (PC) where major pathway components are dynamically enriched. These factors include smoothened (SMO) and patched, which constitute the core reception system for sonic hedgehog (SHH) as well as GLI transcription factors, the key mediators of the pathway. Here, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 70 publications
0
29
0
Order By: Relevance
“…Previous report revealed that bi‐allelic variants of SMO induce development anomalies include dysmorphic facial feature and cardiac defect. Variants have several causes on TMD and ICD: several point mutation, around 30 Kb deletion including SMO exon1 or crucial residues mutation (Le et al, 2020). There are not same residues mutation of current report in the report.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous report revealed that bi‐allelic variants of SMO induce development anomalies include dysmorphic facial feature and cardiac defect. Variants have several causes on TMD and ICD: several point mutation, around 30 Kb deletion including SMO exon1 or crucial residues mutation (Le et al, 2020). There are not same residues mutation of current report in the report.…”
Section: Discussionmentioning
confidence: 99%
“…The role of nonclassical GPCR signaling via SMO in human pathologies is less clearly understood (Arensdorf, Marada, & Ogden, 2016; Qi et al, 2019). Le reported that bi‐allelic variants of SMO in human cause a broad spectrum of developmental anomalies: gelastic epilepsy, hypothalamic hamartoma, dysmorphic facial features and postaxial polydactyly and so forth, due to abnormal Hh signaling (Le et al, 2020). However, the heptahelical domain is the frequent target for recurrent activating mutations in cancer and somatic mosaic mutations in malformation syndromes, such as Curry‐Jones (Ayers and Thérond, 2010; Lam et al, 1999; Taipale et al, 2000; Twigg et al, 2016; Xie et al, 1998), while variation within the remaining domains characteristic of the GPCR superfamily are less frequently observed.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, bi-allelic loss-of-function variations in SMO or Hedgehog acyl-transferase (HHAT) genes in humans led to many developmental anomalies including microcephaly 56,57 . While it is unknown whether microcephaly in humans caused by inactivating mutations in NDE1 is due to abnormally long cilia and/or reduced Hedgehog activity (GLI2), our data lend support to this idea.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the complete absence of SMO or SHH in mouse models resulted in holoprosencephaly because SHH is required for cell migration and axonal guidance in the developing brain. Bi-allelic SMO variations causing the loss of SMO function in humans resulted in variable phenotypes, including hypothalamic hamartomas and microcephaly, shortening of limb bones, narrow chest and heart defects, probably due to defects in HH signalling, which was confirmed in studies of patient fibroblasts [ 113 ].…”
Section: Short-rib Polydactyly Syndromesmentioning
confidence: 94%